(untitled) (Research, Society and Development, 2020)
Objectives: To identify how breastfeeding of children with microcephaly occurs due to congenital Zika syndrome. Methodology: Cross-sectional study, conducted between February and August 2017, with 40 mothers of children with microcephaly treated in a public maternity hospital in the interior of northeastern Brazil. Data collected from a structured instrument, analyzed descriptively. Results: 47.5% of the mothers breastfed their children in the first hour of life, 65% had no difficulties to breastfeed. Gestational age ranged from <37 to >40 weeks, head circumference averaged 31.25 centimeters. The time of diagnosis of microcephaly in 72.5% of the babies was postpartum. There were no statistically significant associations between breastfeeding problems, types of breastfeeding, maternal age and cephalic perimerate of children with microcephaly. Conclusion: Most children with microcephaly due to congenital Zika syndrome were breastfed in the first hour of life. The mothers of these children mentioned as difficulties in breastfeeding, mastitis, nipple fissure and incorrect catch.